Social media use for coping with stress and psychological adjustment: A transactional model of stress and coping perspective - Sun, Xiaobei; Li, Benjamin J.; Zhang, Heng; Zhang, Guanwen (Frontiers in Psychology, 2023)
Introduction The psychological well-being of individuals has become an essential issue during the global pandemic. As a pervasive activity for individuals to pull through COVID-19, social media use may play a role in psychological well-being. Drawing on the transactional model of stress and coping, the current study investigated the relationships between COVID-19-related stressors and the use of social media to facilitate specific coping strategies. We further investigated how social media coping strategies impact users’ psychological adjustment. Methods We collected the data from 641 quarantined residents through a two-wave survey that was conducted in two cities in China during government-mandated lockdowns. Results The results showed that perceived COVID-19 stress was related to the intensity of social media use for problem-focused coping, socioemotional coping, and mental disengagement. In addition, individuals’ psychological adjustment was positively associated with social media use for socioemotional coping and mental disengagement while negatively related to problem-focused coping. Age was also found to be a moderator of the relationship between socioemotional coping and psychological adjustment. Discussion To relieve pandemic-related stress, individuals can actively utilize social media to implement various coping strategies. However, coping activities with social media may not always induce psychological benefits. By revealing the different levels of psychological adjustment among social media users with specific coping strategies, the current research enriched the literature on the effects of social media use on mental health. Findings from this study suggest the need for the prudent use of social media to cope with public health crises.